Case Report: Uterine Adenosarcoma With Sarcomatous Overgrowth and Malignant Heterologous Elements - García-Mendoza, Yunuén I.; Murguia-Perez, Mario; Galván-Linares, Aldo I.; Mendoza-Ramírez, Saulo; García-Salinas, Norma L.; Moctezuma-Ramírez, Julio G.; Murillo-Ortiz, Blanca O.; Bueno-Rosario, Luis Jonathan; Olvera-Olvera, Marco A.; Corredor-Alonso, Guillermo E. (Frontiers in Medicine, 2022)
A 46- year-old woman presented a uterine adenosarcoma originating in the lower uterine segment. The diagnosis was made in an endometrial biopsy and confirmed in the pathological examination of the complete surgical specimen, both identifying heterologous malignant elements. In addition, complementary immunohistochemical studies were performed. We reviewed the literature, illustrating the clinical and morphological characteristics and the differential diagnoses to be evaluated.